STUDI PENGELOLAAN LIMBAH PABRIK GULA (STUDI KASUS PABRIK GULA PT. KEBON AGUNG DI TRANGKIL PATI) - Syafrudin, Syafrudin; Astuti, Arieyanti Dwi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Solid waste from sugar cane which are familiar to call â€œblotongâ€ and â€œketelâ€ dust is potentially toÂ compost. In the composting process, biostarnio activator is added to increase the compostingÂ process. The composting process take + 22 days to produce mature compost and the productÂ has been met the SNI 19 7030-2004, which are N 1,37%; Â P 2 O 5 Â 1,81%; K 2 O 2,22%; Fe 0,49%;Â Ca 2,56%; MgO 0,53%; Mn 0,03%; pH 7,1; Zn 80,99 ppm; Cu 44,01 ppm; C organic 16,48%;Â C/N ratio 12,03 %.